Dinamika Leksikon Flora dan Fauna Bahasa Bali pada Lingkungan Persawahan - Ayu Winda Winanda, Kadek; Dhanawaty, Ni Made; Sri Satyawati, Made (Humanis, 2022)
This study aims (1) to describe the forms of flora and fauna lexicons in the rice field environment in Ubud (2) to find out the flora and fauna lexicons in the rice field environment in Balinese language which were influenced by flora and fauna lexicons in Indonesian language in a speech community in Ubud (3) to find out the factors that cause the lexicon of flora and fauna of the Balinese language was influenced by Indonesian language in the rice field environment in Ubud. This study were used morphological theory, ecolinguistic theory using a logical dimension model proposed by Bang and Døør, as well as ecolinguistic theory, especially ecology of language according to Haugen and ecolinguistic parameters. The method was used to referring the techniques involved proficient. There were three results of this study, namely as follows. First, finding the forms of flora and fauna lexicons in the rice field environment in Ubud, namely single form and complex form, consisting of reapeated and compound words. Second, discovering the flora and fauna lexicon in the rice field environment in Balinese language which was starting to be influenced by the flora and fauna lexicon in the Indonesian language in the speech community of the people in Ubud, namely the  ambengan lexicon, padang getap, keladi, piduh-piduh, ligundi, pacet, blecing, yuyu, blauk, dan kakul. Third, finding the factors causing of the influence of flora and fauna lexicon in the rice field environment in Ubud, namely physical changes in the rice field environment, damage to the ecosystem in the rice field, inheritance of the flora and fauna in the rice field environment in Ubud, and language changes.